High-Resolution Microstructure Analysis of Cork Spot Disordered Pear Fruit “Akizuki” (Pyrus pyrifolia Nakai) Using X-Ray CT - Cui, Zhenhua; Wang, Nannan; Duan, Yanxin; Xu, Xinrui; Wang, Ran; Zhang, Shaoling; Ma, Chunhui (Frontiers in Plant Science, 2021)
Cork spot is one of the most damaging physiological disorders in pear, causing considerable economic loss every year. However, the mechanism of cork spot occurrence needs requires further illustrationexamination. In this study, X-ray CT scanning was applied to analyze the microstructure of pear fruit ‘Akizuki’ (Pyrus pyrifolia), a cultivar susceptible to cork spot disorder, to clarify elucidate the fruit texture alteration before and after cork spot occurredbetween healthy and cork spotted fruit. Results showed that cork spotted fruit had much higher porosity (9.37%) than the healthy one fruit (3.52%). Reconstructed 3D network skeleton models showed highly branched pore channels in the cork spotted fruit and a low degree of pore connectivity in the healthy fruit. Even in the areas of disordered fruit without cork spot of the disordered fruit, the pore throat diameter (77 μm), pore length, (160 μm) and coordinated core number (77 μm, 160 μm, and 16, respectively) (16) were much higher than that of the healthy fruit. Fruit core structure analysis showed that core deformation only happened in cork spotted fruit. A much more highly branched network was observed in the cork spotted fruit cores compared with healthy fruit cores. High-resolution observation ofn the flesh tissue directly demonstrated that pore size in cork spotted fruit (87 μm) was four times larger than that of healthy fruit (22 μm). the 4-time bigger size of the pore in the cork spotted fruit (87 μm) than that of the healthy fruit (22 μm). Altered expression of genes related to Ca2+ transport and uneven distribution of intracellular Ca2+ were also shown to associate with the development of cork spot disorder. Our results suggested that the flesh tissue damage likely occurred happened probably prior to the initiation of cork spot. The dysfunction of long-distance and transmembrane Ca2+ transport channels could be responsible for the imbalanced distribution of Ca2+ inside the fruit, thus resulting in the cork spot development.